Mengeksplorasi Gaya Kepemimpinan Pengepul Kelapa Sawit Mitra Unggul - Stevanus Adi Pratama; Shofia Amin; Dwi Kurniawan (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The leadership style of oil palm collectors plays an important role in improving the welfare of smallholder members. This study aims to describe the leadership style of Mitra Unggul oil palm collectors in the eyes of farmer members, and describe the success of Mitra Unggul leaders in prospering farmer members so that they can master FFB marketing. The research uses a type of qualitative research by conducting direct research in the field. This study uses a subject sampling technique with purposive sampling. The data collection technique uses observation, interview, and documentation methods to obtain accurate data. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of this study show that the leadership style of Mitra Unggul palm oil collectors is included in the charismatic leadership type where Mitra Unggul leaders have the attraction to influence others to achieve common goals